2022
DOI: 10.1007/s00332-022-09801-0
|View full text |Cite
|
Sign up to set email alerts
|

tgEDMD: Approximation of the Kolmogorov Operator in Tensor Train Format

Abstract: Extracting information about dynamical systems from models learned off simulation data has become an increasingly important research topic in the natural and engineering sciences. Modeling the Koopman operator semigroup has played a central role in this context. As the approximation quality of any such model critically depends on the basis set, recent work has focused on deriving data-efficient representations of the Koopman operator in low-rank tensor formats, enabling the use of powerful model classes while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…A tensor-based formulation of gEDMD, which can be regarded as a combination of the methods presented in Klus et al (2020b) and Nüske et al (2021), for the approximation of the Koopman generator is described in Lücke and Nüske (2022).…”
Section: Tensor-based Variantsmentioning
confidence: 99%
“…A tensor-based formulation of gEDMD, which can be regarded as a combination of the methods presented in Klus et al (2020b) and Nüske et al (2021), for the approximation of the Koopman generator is described in Lücke and Nüske (2022).…”
Section: Tensor-based Variantsmentioning
confidence: 99%
“…[19][20][21] The idea behind this format is to decompose a high-dimensional tensor into a chain-like network of lower-dimensional tensors, which enables us to simulate and analyze large-scale problems if the underlying coupling structure allows for low-rank decompositions. Several applications of tensor trains-which can be considered as a special case of the ansatz used in the multi-layer (ML) variant of MCTDH 15,16 mentioned above-and tensor-train operators have shown that it is possible to mitigate the curse of dimensionality and to tackle high-dimensional problems, which cannot be solved using conventional numerical methods, see, e.g., dynamical systems, 22,23 system identification, 24,25 quantum mechanics, [26][27][28] and also quantum machine learning. 29,30 Typically, the applications require the approximation of the solutions of systems of linear equations, eigenvalue problems, and ordinary/partial differential equations.…”
Section: Introductionmentioning
confidence: 99%